2004
DOI: 10.1096/fj.03-0978fje
|View full text |Cite
|
Sign up to set email alerts
|

Diet‐induced insulin resistance promotes amyloidosis in a transgenic mouse model of Alzheimer's disease

Abstract: Recent epidemiological evidence indicates that insulin resistance, a proximal cause of Type II diabetes [a non-insulin dependent form of diabetes mellitus (NIDDM)], is associated with an increased relative risk for Alzheimer's disease (AD). In this study we examined the role of dietary conditions leading to NIDDM-like insulin resistance on amyloidosis in Tg2576 mice, which model AD-like neuropathology. We found that diet-induced insulin resistance promoted amyloidogenic beta-amyloid (Abeta) Abeta1-40 and Abeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
441
6
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 585 publications
(491 citation statements)
references
References 46 publications
(52 reference statements)
34
441
6
3
Order By: Relevance
“…Some experimental studies support the notion that HFD‐induced obesity exacerbates cerebral pathological alterations and the accompanying cognitive deficit in APP transgenic mice (Ho et al, 2004). In wild‐type mice, some studies suggest that HFD impairs cognition (Winocur & Greenwood, 2005) while other claim for no effect (Kesby et al, 2015) or even improvement of memory (Coscina et al, 1986) and protection from age‐related cognitive decline (Scheibye‐Knudsen et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Some experimental studies support the notion that HFD‐induced obesity exacerbates cerebral pathological alterations and the accompanying cognitive deficit in APP transgenic mice (Ho et al, 2004). In wild‐type mice, some studies suggest that HFD impairs cognition (Winocur & Greenwood, 2005) while other claim for no effect (Kesby et al, 2015) or even improvement of memory (Coscina et al, 1986) and protection from age‐related cognitive decline (Scheibye‐Knudsen et al, 2014).…”
Section: Discussionmentioning
confidence: 79%
“…The impact of HFD on memory and cognition is also controversial and depends on the composition of the fat and the time of exposure to HFD. Some experimental studies support the notion that HFD‐induced obesity exacerbates cerebral pathological alterations and the accompanying cognitive deficit in APP transgenic mice (Ho et al, 2004) while other claim for no effect (Kesby et al, 2015) or even improvement of memory in mice (Coscina, Yehuda, Dixon, Kish, & Leprohon‐Greenwood, 1986). …”
Section: Introductionmentioning
confidence: 92%
“…Alzheimer's disease is the most common form of dementia, characterised by loss of recent memory as one of the first symptoms and a progressive decline in all cognitive skills later on in the disease [3,26]. Considerable evidence suggests that insulin resistance and obesity may directly contribute to the pathogenesis of Alzheimer's disease [27][28][29][30][31]. However, not much emphasis has been put on the role of Alzheimer's disease in obesity and type 2 diabetes development, as characterised by insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…We found that under HFD feeding conditions, basal S6 phosphorylation was significantly higher in brains from PSEN1 and APP/PSEN1 mice and was as high as the insulin-stimulated S6 phosphorylation observed in wildtype mice, consistent with the insulin resistance observed in Alzheimer's disease mice. Since a decrease in insulinstimulated Akt/PKB phosphorylation was observed in other mouse models of Alzheimer's disease in specific regions of brain or peripheral tissues [16,28], we examined Akt/PKB phosphorylation from whole-brain lysates, finding, as expected from their impaired glucose tolerance, that insulin-stimulated Akt/PKB phosphorylation was decreased in PSEN1 and APP/PSEN1 mice under chow as well as HFD feeding conditions. In addition, insulin-stimulated phosphorylation of ERK1 and -2 was downregulated in PSEN1 and APP/PSEN1 mice in comparison to wild-type controls, both on chow and HFD.…”
Section: Discussionmentioning
confidence: 99%
“…3B). 44 At first, this result may seem at odds with earlier studies that attributed high-fat diets to increased A␤ loads 46,47 ; however, in these earlier studies, fat was added to the diet without substantial decrease in carbohydrate content. It is unlikely these animals produced KB.…”
Section: Ketogenic Dietsmentioning
confidence: 93%